Increased Total Serum Random Cortisol Levels Predict Mortality in Critically Ill Trauma Patients. Issue 11 (November 2014) - Pandya, Urmil; Polite, Nathan; Wood, Teresa; Lieber, Michael
Dysfunction in the hypothalamopituitary adrenal axis is thought to exist; however, there continues to be controversy about what level of serum cortisol corresponds to adrenal insufficiency. Few studies have focused on the significance of serum random cortisol in the critically ill trauma patient. Trauma patients with total serum random cortisol levels drawn in the intensive care unit within the first seven days of hospitalization were retrospectively reviewed. The primary outcome measured was in-hospital mortality. Two hundred forty-two patients were analyzed. Non-survivors had significantly higher mean cortisol levels than survivors (28.7 ± 15.80 mg/dL vs 22.9 ± 12.35 mg/dL, P = 0.01). Patients with cortisol 30 mg/dL or greater were more likely to die with odds ratio of 2.7 (95% confidence interval [CI], 1.5 to 5). The odds ratio increased to 4.0 and 3.8 (95% CI, 1.4 to 11.4 and 1.3 to 10.9) when cortisol was drawn on hospital Day 2 and Days 3 through 7, respectively. Among nonsurvivors, patients with an injury severity score less than 25 had significantly higher cortisol levels than patients with an Injury Severity Score 25 or higher (35.3 ± 19.21 mg/dL vs 25.7 ± 13.21 mg/dL, P = 0.009). Patients with massive transfusion, traumatic brain injury, spinal cord injury, or solid organ injury did not have significantly different cortisol levels. The covariate-adjusted area under the receiver operating characteristic curve indicated that cortisol level has a 77 per cent accuracy in differentiating survivors from nonsurvivors. Higher cortisol levels were predictive of mortality in critically ill trauma patients. Whether serum cortisol level is a marker that can be modified remains an area of interest for future study.